Case Report: The great mimicker: cerebral syphilitic gumma - Liu, Jiahui; Sun, Kun; Deng, Yanxia; Ding, Lianshu (Frontiers in Medicine, 2025)
Cerebral syphilitic gumma, a rare form of neurosyphilis, poses significant diagnostic challenges due to its imaging similarities to gliomas and brain metastases. This report details the diagnostic and therapeutic journey of a patient with cerebral syphilitic gumma admitted to the Department of Neurosurgery, Nanjing Medical University Affiliated Huaian First Hospital in February 2025. Initially misdiagnosed with a brain malignancy, the accurate diagnosis was established intraoperatively and confirmed postoperatively through histopathological examination. This case highlights the importance of considering neurosyphilis in differential diagnoses of intracranial lesions, especially when conventional imaging and clinical presentations are inconclusive.